Інженерія вимог та планування розробки продукту для відбору контенту зовнішньої реклами - Щербина, В. Є. (ХНУРЕ, 2023)
The successful creation of any software product, including content selection systems for outdoor advertising, requires careful planning and development of requirements and product development planning that affect the entire life cycle of the software product. They allow developers to understand exactly what functions the product must perform and what requirements it must satisfy, which ensures high quality and usability of the product. Insufficient attention to these steps can lead to problems with product functionality, delays in development timelines, and poor compliance with customer and user requirements. The paper will consider the key stages of this process for creating a system for selecting outdoor advertising content.